Investigation of the Influence of Al2O3 Particles on the Microhardness and Tensile Strength of PA6 Composites - Jeng-Huang, Song; Geo, Angelo; Kannaiyan, Sathiyalingam; Tanoto, Yopi Yusuf (Journal of Research Updates in Polymer Science, 2024)
Polyamide is a high-performance synthetic plastic known for its strength, durability, flexibility, chemical resistance, and low cost, making it widely used in engineering, automotive, and electrical. However, the surface and mechanical properties can be further enhanced to meet the growing demands of advanced engineering applications. This study aims to investigate the influence of Al2O3 particles on the hardness of polyamide 6 (PA6). The Al2O3 was mixed with PA6 at weight percentages (wt.%) of 0.3% and 1.5% then were fabricated into composite plates using compression molding and subsequently. As a result, the composites achieved higher microhardness and tensile strength compared to the matrix with increases of 13.3% and 7.3% achieved by incorporating 0.3 wt.% of reinforcement, respectively. This result suggests that Al2O3 has the potential to improve the surface properties and mechanical strength of the matrix material.